Striking changes in tea metabolites due to elevational effects. (30th October 2018) - Kfoury, Nicole; Morimoto, Joshua; Kern, Amanda; Scott, Eric R.; Orians, Colin M.; Ahmed, Selena; Griffin, Timothy; Cash, Sean B.; Stepp, John Richard; Xue, Dayuan; Long, Chunlin; Robbat, Albert
Highlights: Tea metabolite concentrations were strikingly different at high and low elevations. 37 volatile and 4 non-volatile metabolites statistically differentiated the teas. GC–GC/MS-olfactometry was used to detect sensory-active compounds. Abstract: Climate effects on crop quality at the molecular level are not well-understood. Gas and liquid chromatography–mass spectrometry were used to measure changes of hundreds of compounds in tea at different elevations in Yunnan Province, China. Some increased in concentration while others decreased by 100's of percent. Orthogonal projection to latent structures-discriminant analysis revealed compounds exhibiting analgesic, antianxiety, antibacterial, anticancer, antidepressant, antifungal, anti-inflammatory, antioxidant, anti-stress, and cardioprotective properties statistically (p = 0.003) differentiated high from low elevation tea. Also, sweet, floral, honey-like notes were higher in concentration in the former while the latter displayed grassy, hay-like aroma. In addition, multivariate analysis of variance showed low elevation tea had statistically (p = 0.0062) higher concentrations of caffeine, epicatechin gallate, gallocatechin, and catechin; all bitter compounds. Although volatiles represent a small fraction of the total mass, this is the first comprehensive report illustrating how normal variations in temperature, 5 °C, due to elevational effects impact tea quality.